Improving Students’ Vocabulary Mastery Using Spelling Bee Games at Junior High Level - Afiase, Dwi Rias; Nugroho, Andhi Dwi; Karjono, Johanes Climacus Setyo; Prastanti, Afria Dian; Christanti, Ana (Journal of English Education, Literature and Linguistics, 2023)
This study aimed at finding out to what extent spelling bee games improve vocabulary mastery and explore the advantages and disadvantages of spelling bee games. It discussed the implementation of the spelling bee game in English Language Teaching at the Junior High School. This research implemented spelling bee games as one of the ways to improve students’ vocabulary mastery. This study used the Classroom Action Research (CAR) method which was conducted in two cycles. The researcher used three data collection methods, namely observation, questionnaires, and tests. The data for this study were their written test results by answering questions about the vocabulary they had learned. The data was assessed based on the number of words that the students successfully answered. To determine whether the percentage was high or low, the researcher used the scoring criteria. The results of this study serve as references for future research on spelling bee games, such as benefits, drawback, challenges or opportunities in English language teaching especially at junior high school level.